2018
DOI: 10.1111/bcp.13604
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological treatments for alleviating agitation in dementia: a systematic review and network meta‐analysis

Abstract: Risperidone, serotonin reuptake inhibitors as a class and dextromethorphan/quinidine demonstrated evidence of efficacy for agitation in dementia, although findings for dextromethorphan/quinidine were based on a single RCT. Our findings do not support prescribing haloperidol due to lack of efficacy, or oxcarbazepine due to lack of acceptability. The decision to prescribe should be based on comprehensive consideration of the benefits and risks, including those not evaluated in this meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 91 publications
1
42
0
2
Order By: Relevance
“…For instance, concurrent use of anticholinergic medicines is not recommended with cholinesterase inhibitors; however, the primary pharmacological management for behavioural and psychological disturbances in dementia are antipsychotics such as risperidone. 15,18,[28][29][30][31][32] In our study, the antipsychotic risperidone was the most commonly dispensed medicine with anticholinergic effects both before and after initiating dementia medicines. Under PBS restrictions, risperidone formulations are only eligible for government subsidy for managing behavioural and psychological symptoms of dementia; thus accounting for the substantial number of dispensings captured in our data.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…For instance, concurrent use of anticholinergic medicines is not recommended with cholinesterase inhibitors; however, the primary pharmacological management for behavioural and psychological disturbances in dementia are antipsychotics such as risperidone. 15,18,[28][29][30][31][32] In our study, the antipsychotic risperidone was the most commonly dispensed medicine with anticholinergic effects both before and after initiating dementia medicines. Under PBS restrictions, risperidone formulations are only eligible for government subsidy for managing behavioural and psychological symptoms of dementia; thus accounting for the substantial number of dispensings captured in our data.…”
Section: Discussionmentioning
confidence: 70%
“…This leads to increased challenges for clinicians with ever‐extensive clinical responsibilities and makes it difficult to determine what approach to take. For instance, concurrent use of anticholinergic medicines is not recommended with cholinesterase inhibitors; however, the primary pharmacological management for behavioural and psychological disturbances in dementia are antipsychotics such as risperidone …”
Section: Discussionmentioning
confidence: 99%
“…Atypical antipsychotics is superior compared to placebo in reducing behavioral symptoms in patients with dementia, whereas haloperidol is not [73] and in elderly patients with various conditions, risperidone has been found to be as efficacious as haloperidol [74]. Moreover, several very large observational studies have demonstrated that haloperidol is associated with higher mortality, risk of pneumonia and cardiovascular disease compared to atypical antipsychotics (including risperidone) [53,54].…”
Section: Justification For Recommendationsmentioning
confidence: 99%
“…15 A recent network meta-analysis reported that SSRIs as a class had efficacy for alleviating agitation, but when analysed separately, citalopram was not significantly efficacious. 28 Evaluation of efficacy and the potential for deprescribing should take place after two months. 15 The time to onset of action, importance of adherence, and 15 There is uncertainty about the use of antidepressants in the treatment of depression in Alzheimer's disease.…”
Section: Management Of Bpsdmentioning
confidence: 99%
“…32 For treating agitation/ aggression, risperidone and olanzapine have the strongest evidence, while weaker evidence exists for aripiprazole. 28 Olanzapine and quetiapine have been reported to have the best tolerability. 15 The only antipsychotic currently listed on the PBS for BPSD, including psychotic symptoms and agitation, is risperidone.…”
Section: Management Of Bpsdmentioning
confidence: 99%